Time-resolved measurement of Landau-Zener tunneling in different bases - Tayebirad, Ghazal; Zenesini, A.; Ciampini, D.; Mannella, R.; Morsch, O.; Arimondo, E.; Lörch, N.; Wimberger, Sandro (Physical review. A, Atomic, molecular, and optical physics, 2010)
A comprehensive study of the tunneling dynamics of a Bose-Einstein condensate in a tilted periodic potential is presented. We report numerical and experimental results on time-resolved measurements of the Landau-Zener tunneling of ultracold atoms introduced by the tilt, which experimentally is realized by accelerating the lattice. The use of different protocols enables us to access the tunneling probability, numerically as well as experimentally, in two different bases, namely, the adiabatic basis and the diabatic basis. The adiabatic basis corresponds to the eigenstates of the lattice, and the diabatic one to the free-particle momentum eigenstates. Our numerical and experimental results are compared with existing two-state Landau-Zener models.